Silicosis: Diagnosis and Medicolegal Implications1. Issue 5 (22nd March 2019) - Bukovitz, Brandon; Meiman, Jonathan; Anderson, Henry; Brooks, Erin G.
Abstract: Despite well‐publicized sources of occupational hazard, silicosis continues to threaten industrial workers in the United States. We performed a retrospective search of the University of Wisconsin electronic pathology database to retrieve autopsy cases of silicosis and collaborated with the Wisconsin Department of Health Services to obtain statewide epidemiologic data regarding silicosis morbidity/mortality since 2003. Three silicosis autopsy cases were retrieved: all were men with ≥ 30 years of occupational crystalline silica exposure and similar histologic features of collagenous pulmonary nodules with admixed refractile particles. Overall, our state exceeds the national rate of silicosis‐related hospitalizations and mortality, that is, 10.1 hospitalizations per million WI residents versus 1.2 nationally and 1.2 deaths per million WI residents versus 0.4 nationally. Surveillance is crucial to identify emerging occupational hazards and protect workers. A diagnosis of silicosis must be carefully considered at autopsy since it carries substantial implications for worker's compensation, compensatory losses, and employer liability.